Theoretical investigation of injection-locked differential oscillator - Rapin, V. (RT, 2022)
Application of ingection-locked differential LC oscillator began at the beginning of this century, simultaneously with the advent of an autonomous differential LC oscillator. Currently, synchronized differential LC oscillators are an essential part of not only communication systems, but also many automation and measuring devices. The synchronization mode allows significantly expanding the functional posibility of oscillators. Practical application was found not only for separate fundamentally synchronized oscillators but also for the frequency division and multiplication modes, and more complex devices including several coupled oscillators [1 – 12]. The study of the synchronized differential oscillators is a difficult problem, and a satisfactory method for performing this kind of work has not yet been developed. The lack of an adequate mathematical model, permitting the application of rigorous mathematical methods of the nonlinear theory of electrical oscillations, was the reason for using a simplified approach. Usually it was reduced to a transition to a simpler single- circuit LC oscillator, being equivalent to a differential one. However, no justification for such a transition was provided.
Keywords: oscillator; synchronized oscillators; communication systems; mathematical model